The power of independence - Ekert, A (Nature Publishing Group, 2018)
In the past few years, a number of pleasingly wacky ideas proposed by quantum geeks have been turned into experiments and, we are told, much more is yet to come. Indeed, writing in Nature Communications, Rotem Arnon-Friedman and co-authors1 have now shown that existing technology can reach a seemingly impossible scenario where devices of unknown or dubious provenance, even manufactured by enemies, are safely used for secure communication.